Obesity as Risk Factor of Type 2 Diabetes Mellitus in Women of Reproductive Age - Hanifah Ardiani; Soeharyo Hadisaputro; Djoko Trihadi Lukmono; Heri Nugroho; Antono Suryoputro (Global Medical & Health Communication (GMHC), 2018)
Women of childbearing age with type 2 diabetes mellitus (DM) are more at risk of having pregnancy complication (in both the mother and the baby) at twice the risk for sexual dysfunction and three times more likely to die than women of childbearing age without DM. The purpose of this study was to prove obesity as the risk factor of type 2 DM in women of childbearing age. The study design was a case-control and a qualitative analysis using the in-depth interview. This study conducted in Internal Medicine Polyclinic and Eye Polyclinic in Regional General Hospital Madiun, June–July 2017. The population in this study was women of childbearing age 20–49 years old and married who check blood sugar in Regional General Hospital Madiun. The samples of this study were 54 cases and 54 controls using consecutive sampling. Data analyzed by chi-square and logistic regression. The results showed that obese women of childbearing age had risk 2.63 times greater for type 2 DM than non-obese (p=0.016, 95% CI=1.06–6.53). In conclusion, obesity was a risk factor of type 2 DM in the women of reproductive age. OBESITAS SEBAGAI FAKTOR RISIKO DIABETES MELITUS TIPE 2 PADA WANITA USIA SUBURWanita usia subur (WUS) dengan diabetes melitus (DM) tipe 2 lebih berisiko mengalami komplikasi kehamilan (baik pada ibu maupun bayinya), berisiko 2 kali lebih besar untuk menderita gangguan fungsi seksual, dan 3 kali lebih besar untuk mengalami kematian dibanding dengan WUS tanpa DM. Tujuan penelitian ini membuktikan obesitas sebagai faktor risiko DM tipe 2 pada WUS. Desain studi dalam penelitian ini adalah kasus kontrol yang diperdalam dengan analisis kualitatif menggunakan wawancara mendalam. Penelitian ini dilakukan di poliklinik penyakit dalam dan poliklinik mata RSUD Kota Madiun Juni–Juli 2017. Populasi dalam penelitian ini adalah WUS berusia 20–49 tahun dan sudah menikah yang diperiksa gula darah di RSUD Kota Madiun. Sebanyak 54 kasus dan 54 kontrol dipilih menggunakan consecutive sampling. Data dianalisis dengan chi square dan regresi logistik. Hasil penelitian menunjukkan bahwa WUS yang obesitas memiliki risiko 2,63 kali lebih besar untuk mengalami DM tipe 2 dibanding dengan yang tidak obesitas (p=0,016; 95% IK=1,06−6,53). Simpulan, obesitas merupakan faktor risiko DM tipe 2 pada WUS.